KUALITAS PELAYANAN PENGUJIAN KENDARAAN BERMOTOR DI DINAS PERHUBUNGAN KABUPATEN SUKOHARJO - Taufiq Anwar Syaifuddin; Winarti Winarti; Maya Sekar Wangi (Master of Public Administration, Universitas Slamet Riyadi, 2020)
The Department of Transportation, as a regional apparatus organization taskedwith providing services in the field of transportation especially in ensuring thefeasibility and safety of transportation, plays an important role in increasing thestandardization of the feasibility of transport vehicles on the road. Humanresources, in this case the state civil apparatus, are required to be able to provideservices that meet the principles of transparency, accountability, andtrustworthiness in line with the law number 22 of 2009 article 48 concerningTraffic and Road Transportation. The objective of this research is to describe andanalyze the quality of motor vehicle testing services in the Department ofTransportation of Sukoharjo Regency. In this research, the researcher used threeservice indicators, namely: Tangibles, Reliability, Responsiveness, Assurance,and Empathy. The type of this research was descriptive qualitative. The researchwas conducted at the Department of Transportation of Sukoharjo Regency. Thedata used were primary and secondary data. Data collection was done byconducting interviews, observation, and documentation. Data analysis techniquesused were the interactive model of Miles and Huberman. In testing the validity ofthe data, the esearcher used the triangulation technique.